Isolation and Identification of Secondary Metabolic Compounds Acetone Extract from Dutch Eggplant (Cyphomandra betacea) - Mawardi (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2022)
Isolation and identification of secondary metabolite compound in acetone extract from fruit terong belanda (Cyphomandra betacea) have been carried out. The aim of this research is to isolate and identify the secondary metabolite compound in acetone extract from fruit terong belanda (Cyphomandra betacea) which obtain from Enrekang. The compound was obtained by isolation process that consist of several stages, including extraction, fractination, purification and identification. Extraction was carried out using maceration with acetone. The identification was coment by is color test, melt point, solubility and TLC. Base of identification are obtained compound in white powder with melting point 130-131 oC, and positively to the reagent Dragendorf and Wagner gives a brown precipitate that indicated as a alkaloid group. This result is supported by solubility compounds.